DEVELOPMENT OF PROBLEM-BASED LEARNING-BASED MATHEMATICS WITH THE ASSISTANCE OF GEOGEBRA APPLICATIONS TO IMPROVE STUDENTS' MATHEMATICAL CONCEPTS UNDERSTANDING ABILITY - Najwah Rokan; Putri Elmania; Feri Gunawan Sihombing; Asiatul Mardiah Hasibuan; Nur Rahmi Rizqi; Nur Rahmi Rizqi (Universitas Labuhanbatu, 2023)
This research is a development research (R & D) that aimsÂ toÂ improve students' ability to understand mathematical concepts with learning media assisted byÂ problem-based learningÂ geogebra applications.Â The benefit of this research is that students can foster their learning interest in learning mathematics with the help of geogebra application technology so that students can be active in learning and think logically and broadly. This research uses a developmentÂ researchÂ methodÂ with a